THE EFFECT OF ENGLISH SPEECH ACTIVITY TOWARD THE PSYCHOLOGICAL ASPECT IN SPEAKING ENGLISH FOR THE SECOND SEMESTER STUDENTS OF ENGLISH DEPARTMENT AT UNIVERSITAS SULAWESI BARAT - Aco Syarif; Muthmainnah Muthmainnah (UIN Alauddin Makassar, 2017)
Abstract This research is aimed at finding out: (1) whether or not the use of English speech activity effects the students’ motivation for the second semester students of English Department at Universitas Sulawesi Barat and (2) whether or not the second semester students of English Department at Universitas Sulawesi Barat are interested in speaking English through English speech activity. This research applied quasi-experimental research method. The population of the research was all second semester students of English Department at Universitas Sulawesi Barat. The researcher chose class II.A as experimental group (16 students) and class II.B as control group (16 students) as sample of the research. The data of the research were collected by using two kinds of instruments, namely speaking test and questionnaire. Speaking test (interview) was used to obtain data of the students’ speaking ability and questionnaire was used to know the students interest in speaking through English speech activity. The result of data analysis showed that there was significant difference between the students’ score who were taught by using English speech activity and re-telling. It was proved by the mean score of the experimental class which was higher than control group in posttest (79.06>73.37). Based on data analysis, the researcher concluded that: the use of English speech activity can improve students’ speaking ability and make the students interested in speaking English. Abstrak Penelitian ini bertujuan untuk menemukan apakah: (1) penggunaan teknik pidato bahasa Inggris secara signifikan dapat mempengaruhi motivasi mahasiswa semester dua jurusan bahasa Inggris di Universitas Sulawesi Barat dan (2) mahasiswa semester dua jurusan bahasa Inggris di Universitas Sulawesi Barat tertarik belajar bahasa Inggris dengan teknik pidato bahasa Inggris.Penelitian ini menerapkan metode kuasi-eksperimental. Populasi penelitian ini adalah mahasiswa semester dua jurusan bahasa Inggris di Universitas Sulawesi Barat. Peneliti memilih kelas II.A sebagai grup eksperimen (16 siswa) dan II.B sebagai grup control (16 siswa) sebagai sampel penelitian. Data yang diolah dengan menggunakan dua instrumen penelitian yaitu test berbicara dan kuesioner. Test berbicara (wawancara) digunakan untuk memperoleh data kemampuan berbicara sementara kuesioner atau angket digunakan untuk menggunakan ketertarikan siswa dalam menggunakan teknik pidato bahasa Inggris.Hasil analisis data menunjukkan bahwa prestasi belajar mahasiswa berbeda secara signifikan antara mahasiswa yang diajar dengan menggunakan teknik pidato bahasa Inggris dan re-telling. Ini ditunjukkan dengan peroleh nilai rata-rata mahasiswa kelas eksperimen lebih tinggi dari kelas control pada tes akhir (79.06>73.37). Berdasarkan analisis data diatas maka peneliti menyimpulkan bahwa: penggunaan teknik pidato bahasa Inggris dapat meningkatkan kemampuan berbicara siswa dan juga dapat membuat siswa tertarik belajar bahasa Inggris